Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4018/ijdet.2019040103
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Quality in Online/Blended Courses to American and Malaysian Administrators, Faculty, and Students

Abstract: This article compares two studies, investigating administrator, faculty, and student perceptions of quality in online/blended courses conducted in two different contexts, namely (1) two midsize public universities in the United States, and (2) a college in a public university in Malaysia. The research question explored in both studies was: What is the meaning of “quality” in an online/blended course to administrators, faculty, and students? Survey data from the three constituents in both contexts were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…For example, an orientation video can be used to provide the overview of course expectations, demonstrate how to navigate through the course, and the syllabus and course calendar (Martin et al, 2018). This step is critical for student success in the online learning environment (Smidt et al, 2017) and minimizes confusion and frustration (Trammell & LaForge, 2017). Expectations of netiquette should be addressed and emphasized in the orientation as well to promote online civility (Quality Matters, 2018).…”
Section: Traditional Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an orientation video can be used to provide the overview of course expectations, demonstrate how to navigate through the course, and the syllabus and course calendar (Martin et al, 2018). This step is critical for student success in the online learning environment (Smidt et al, 2017) and minimizes confusion and frustration (Trammell & LaForge, 2017). Expectations of netiquette should be addressed and emphasized in the orientation as well to promote online civility (Quality Matters, 2018).…”
Section: Traditional Classroommentioning
confidence: 99%
“…Price et al (2016) advise that attention should be paid to providing appropriate constructive feedback and promoting diverse thinking; learning occurs through debate of ideas and developing a defense for one's position. Interaction on the class discussion board is equally important; making it personalized assures students that their instructor is actively engaged (Smidt et al, 2017). Class discussions that are personal and collaborative contribute to a student-centered environment and create a sense of community (Poll et al, 2014).…”
Section: Instructor Presencementioning
confidence: 99%
See 1 more Smart Citation
“…This approach, through its activity structure, enforces discursive interactions about problems and their solutions. These afford both the necessary presence and communication for effective online learning experiences (Smidt et al, 2017). The advantage of many learner-centered approaches is that they create the necessary contexts for communication and presence that are required online.…”
Section: Discussionmentioning
confidence: 99%
“…Even teachers came to appreciate the relative advantages of online learning. In fact, other research has shown positive impacts particularly for access to instruction in low socio-economic and developing countries (Smidt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%